2003
DOI: 10.1128/mcb.23.4.1368-1378.2003
|View full text |Cite
|
Sign up to set email alerts
|

Dual Roles for Spt5 in Pre-mRNA Processing and Transcription Elongation Revealed by Identification of Spt5-Associated Proteins

Abstract: During transcription elongation, eukaryotic RNA polymerase II (Pol II) must contend with the barrier presented by nucleosomes. The conserved Spt4-Spt5 complex has been proposed to regulate elongation through nucleosomes by Pol II. To help define the mechanism of Spt5 function, we have characterized proteins that coimmunopurify with Spt5. Among these are the general elongation factors TFIIF and TFIIS as well as Spt6 and FACT, factors thought to regulate elongation through nucleosomes. Spt5 also coimmunopurified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
253
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(289 citation statements)
references
References 67 publications
23
253
2
Order By: Relevance
“…Thus the MED31/SOH1 subunit of the Mediator displays genetic interactions not only with Pol II (34), but also with TFIIB (34) and several transcription elongation factors that include SII (35), the last in turn displaying close relationships with hSpt4-hSpt5/DSIF (36)(37)(38)(39). Furthermore, consistent with its role in early elongation, TFIIB has also been connected to diverse elongation and processing factors (40).…”
Section: Discussionmentioning
confidence: 90%
“…Thus the MED31/SOH1 subunit of the Mediator displays genetic interactions not only with Pol II (34), but also with TFIIB (34) and several transcription elongation factors that include SII (35), the last in turn displaying close relationships with hSpt4-hSpt5/DSIF (36)(37)(38)(39). Furthermore, consistent with its role in early elongation, TFIIB has also been connected to diverse elongation and processing factors (40).…”
Section: Discussionmentioning
confidence: 90%
“…Following initiation, RNA Pol II transcribes at varying rates and undergoes conformational changes during transcript elongation that may result in pausing at particular loci (for review, see Arndt and Kane 2003). Many connections between transcription and RNA processing have been found to occur during transcription elongation (Howe et al 2003;Lindstrom et al 2003). A recent study suggested cotranscriptional specificity for RNA binding proteins; some splicing factors were constitutively recruited while others depended on the splicing outcome (Mabon and Misteli 2005).…”
mentioning
confidence: 99%
“…Spt5 binds directly to the triphosphatase and guanylyltransferase components of the capping apparatus in mammals and in the fission yeast S. pombe (27,28). Connections between capping enzymes and Spt5 have also been reported in S. cerevisiae (29). The interactions of the S. pombe triphosphatase (Pct1) and guanylyltransferase (Pce1) enzymes have been studied in vivo and in vitro using twohybrid assays and purified recombinant proteins, respectively (28).…”
mentioning
confidence: 99%